Soothing Properties of Glycerol in Cough Syrups for Acute Cough Due to Common Cold - Ronald Eccles; Pascal Mallefet (MDPI AG, 2017)
The treatment and management of acute cough due to common cold costs billions of dollars of healthcare expenditure and there is a growing opinion that a simple linctus containing glycerol with flavourings such as honey and lemon is a safe and effective treatment for acute cough in children and adults. Glycerol is a component of most cough syrups, and although it is often thought of only as a solvent or thickening agent in cough syrups, it may be a major component for the efficacy of cough syrups due to its special properties of lubrication, demulcency, sweetness, and acting as a humectant. The major benefit of cough syrups in soothing cough is likely due to the properties of the syrup rather than the active ingredients and this review discusses the special properties of glycerol in relation to the treatment of acute cough.